Dorsal Approach for Management of Complex Kaplans Dislocation - Khanal, Siddhartha; Panthi, Sagar; Shrestha, Rishiswor; Neupane, Bikash; Pradhan, Jigyasu (Journal of Nepal Health Research Council, 2023)
Complex metacarpophalangeal dislocation is an uncommon injury where the index is the most commonly involved finger. The most common mechanism involves hyperextension of digits at the metacarpophalangeal joint. Such dislocation needs open reduction as the volar plate becomes entrapped between the metacarpal head and proximal phalanx making close reduction difficult. Approaches for open reduction can be dorsal, volar, and lateral. In our patient, we commenced a dorsal approach for reduction and additional stabilization done with K-wire. An early range of movement was initiated and resulted in good functional recovery. Keywords: Dislocation; metacarpophalangeal; plate; volar.